COMPARISONS OF ANTHROPOMETRIC CHARACTERISTICS AND SOME PERFORMANCE PARAMETERS OF PRE-ADOLESCENT TENNIS PLAYERS AND SEDENTARY - Bingöl Dıedhıou, Azize; Andre, Hülya; Akca, Firat (My University, 2023)
This study aimed to investigate the anthropometric and somatotype characteristics, explosive power and agility characteristics of tennis-player and sedentary girls and boys age between 10-12. Participants were separated by gender and formed as experımental group (EG) and control group CG). Body weight (BW), body mass index (BMI), body fat percentage (BFP) and somatotype characteristics of the participants were determined. Then the agility test and to evaluate the explosive power the standing long jump test was applied. Statistical analyses were performed with SPSS software version 22.0. After the descriptive statistics of the participants were determined, whether the data showed normal distribution was evaluated with the Shapiro-Wilk test. T-test for independent samples was applied. Effect sizes (Cohen’s d) were also calculated for each dependent variable. The statistical significance value was accepted as p<0.05. The study findings examination according to the sport status variable in the height, BW, BMI and BFP showed no statistically significant difference between the groups (p>.05). The somatotype characteristics were evaluated, no statistically significant difference was observed between the EG and CG in both genders p>.05. The performance tests were examined, there was no statistically significant difference between the girl pre-adolescents groups in the standing long jump test, while a statistically significant difference was found between the groups in favor of those EG in boy pre-adolescents (pG=.589; pB=.012). In the agility test, there was a statistically significant difference in favor of EG in both genders (pG=.000; pB=.000). As a result, it was observed that there was no difference among the EG and CG in terms of anthropometric and somatotype characteristics in both genders (p>.05). However, it was observed that the explosive power and agility characteristics of pre-adolescent boys EG were better than the CG (p<.05). On the other hand, it was observed the agility characteristics of pre-adolescent girls were better in EG compared to CG (p<.05).
Keywords: Agility; somatotype; anthropometric characteristic; explosive power; pre-adolescent; tennis.